2017
DOI: 10.1111/bjdp.12182
|View full text |Cite
|
Sign up to set email alerts
|

The development and correlates of gender role attitudes in African American youth

Abstract: This research examined the longitudinal trajectories and family correlates of gender role attitudes in African American youth in a sample of 166 sibling pairs residing with their mothers and fathers. Multilevel modelling revealed that (1) girls and boys exhibited significant declines in gender attitude traditionality from ages 9 to 15 that levelled off through age 18, (2) mothers' (but not fathers') gender role attitude traditionality was positively related to youth's attitude traditionality, and (3) within-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 52 publications
1
17
1
Order By: Relevance
“…The remaining systems in the ecological model represent distal contexts that children do not participate in, such as parents’ social interactions outside the home. For instance, a study of gender attitude development among African-American adolescents found that when mothers reported increased instances of perceived racial discrimination, their children reported less support for restrictive gender norms (Lam et al, 2017). By demonstrating the link between multiple domains of inequalities, these findings highlight the value of studying gender attitude development in diverse contexts, with different patterns of systemic injustice tied to marginalized identities.…”
Section: Individual and Contextual Predictors Of Gender Attitude Deve...mentioning
confidence: 99%
“…The remaining systems in the ecological model represent distal contexts that children do not participate in, such as parents’ social interactions outside the home. For instance, a study of gender attitude development among African-American adolescents found that when mothers reported increased instances of perceived racial discrimination, their children reported less support for restrictive gender norms (Lam et al, 2017). By demonstrating the link between multiple domains of inequalities, these findings highlight the value of studying gender attitude development in diverse contexts, with different patterns of systemic injustice tied to marginalized identities.…”
Section: Individual and Contextual Predictors Of Gender Attitude Deve...mentioning
confidence: 99%
“…One longitudinal study of African‐American youth's gender attitudes regarding marital roles was based on the same data set used here. Results from that study showed that girls exhibited less traditional gender attitudes than boys, and consistent with a gender schema perspective, youth's traditional attitudes declined from ages 9 to 15 and leveled off in later adolescence (Lam, Stanik, & McHale, ).…”
Section: The Course Of Adolescent Gender Developmentmentioning
confidence: 85%
“…In a seven-round longitudinal study examining changes in gender attitudes from ages 7 to 19 years, Crouter et al [20] observed that most adolescents' gender attitudes became more equitable, but that variation exists by individual (e.g., sex, age, and birth order) and contextual (e.g., parents' gender attitudes and sibling sex) factors. Lam et al [24], in a 3-year longitudinal study among African American adolescents, found that both girls' and boys' gender attitudes became significantly more equitable from ages 9 to 15 years and then leveled off through age 18 years. In this study, mothers', but not fathers', gender attitudes were correlated with their children's gender attitudes.…”
Section: Conflicts Of Interestmentioning
confidence: 99%